A case report of bosutinib-induced interstitial granulomatous drug reaction in a patient with chronic myelogenous leukemia: a case report - Aria, Alexander B (SAGE Open Med Case Rep, 2018)
Bosutinib is a BCR-ABL tyrosine kinase inhibitor approved for the treatment of Philadelphia chromosome–positive chronic myelogenous leukemia. We report a case of bosutinib-induced interstitial granulomatous drug reaction in a 50-year-old Caucasian female with chronic myelogenous leukemia. Histologic analysis of a punch biopsy showed diffuse interstitial granulomatous infiltrates consisting of histiocytes amid thickened collagen accompanied by eosinophils. Her lesions improved with clobetasol 0.05% cream. No cases describing BCR-ABL tyrosine kinase inhibitor–associated interstitial granulomatous drug reaction were found in a search of the literature. It is important for physicians to be aware of the risk of interstitial granulomatous drug reaction associated with bosutinib treatment.